Teaching the History of Nursing in Nursing undergraduate courses in Alagoas (Research, Society and Development, 2022)
This research aims to analyze the teaching of Nursing History in undergraduate nursing courses in Alagoas. It is a documentary, descriptive, historical study, anchored in the perspective of the History of the Present Time, having the State of Alagoas as a scenario. The sample consisted of 15 undergraduate nursing courses, data collection took place from October to December 2019. The data were presented with the help of statistical resources and techniques, and the discussion took place in the light of the relevant literature. The term “Nursing History” is no longer used in the analyzed curricula; the teaching of the Nursing History discipline is based on the historical process of the profession since its creation and uses active and problematizing methodologies; most professors have a master's or doctorate degree; the teaching modality is mostly face-to-face, with a workload that varies from 18 to 52 hours, being offered predominantly in the initial stages of the course. The History of Nursing is a fundamental element in the teaching-learning process, especially in the construction of the professional identity of the nursing student, thus making the teaching of this area of knowledge indispensable in terms of preserving the historical memory of the profession and development. and improvement of skills in their technical-scientific practice.